Environmental evolution and fire history of Rebun Island (Northern Japan) during the past 17, 000 years based on biomarkers and pyrogenic compound records from Lake Kushu. (20th June 2022) - Yamamoto, Masanobu; Wang, Fangxian; Irino, Tomohisa; Yamada, Kazuyoshi; Haraguchi, Tsuyoshi; Nakamura, Hideto; Gotanda, Katsuya; Yonenobu, Hitoshi; Leipe, Christian; Chen, Xuan-Yu; Tarasov, Pavel E.
Abstract: Rebun is a small island located northwest of Hokkaido Island where hunter-fisher-gatherer cultural traditions continued until the 19th century CE. In this study, we quantified polycyclic aromatic hydrocarbons (PAHs), pentacyclic triterpene methyl ethers (PTMEs), n -fatty acids, and glycerol dialkyl glycerol tetraethers (GDGTs) in sediments from Lake Kushu in northern Rebun Island to reconstruct changes in limnology, the local environment and local to regional fire activities during the past 17, 000 years (i.e., 17 ka). The PAH concentration increased from 11 to 10 cal ka BP. PAH and PTME compositions indicate that this change was associated with an increase of fire activity at proximal locations (i.e., the vicinity of Lake Kushu) and a change in the composition of grasses growing around the lake. A peak in PAH concentrations at 6.6–6.0 cal ka BP likely indicates intensive fire activity on Rebun Island. The PAH composition after 6 cal ka BP mainly reflected the combustion of conifers near the lake. The GDGTs, n -fatty acids, perylene, and PTME concentrations were higher around 10 cal ka BP and after 6 cal ka BP compared to the remaining periods, suggesting better preservation of those compounds under lake conditions marked by lower oxygen concentrations.